107k views
3 votes
Average rate of change for the function from 1 to 4.

H(x)=x^3-1

Average rate of change for the function from 1 to 4. H(x)=x^3-1-example-1
User Kett
by
6.2k points

1 Answer

5 votes

Answer:

A. 21

Explanation:

First, find h(1) and h(4) given the function,
h(x) = x^3 - 1


h(1) = (1)^3 - 1 = 1 - 1


h(1) = 0


h(4) = (4)^3 - 1


h(4) = 64 - 1


h(4) = 63

Average rate of change =
(h(b) - h(a))/(b - a)

Where,


a = 1, h(a) = 0


b = 4, h(b) = 63

Average rate of change =
(63 - 0)/(4 - 1)


= (63)/(3) = 21

User Mohsen Haddadi
by
5.3k points